Penyalahgunaan Dadah di Kampus - Awang, Amir (Penerbit Universiti Sains Malaysia, 1979)
This paper begins by stating that drug abuse in the campus is a real but elusive problem. It needs to be tackled early. To do so, it first clarifies the meaning of "drug abuse" and then examines possible causes of drug abuse, based on scientific studies as well as observations from various sources. Having done so, it suggests a number of possible lines of action to detect and to prevent drug abuse among university students. Finally it emphasises the need for motivation to change within the afflicted self, without which any corrective step taken may not be very effective.